ZONAL CRYSTALS OF BRITHOLITE: METASOMATISM OR CRYSTALLIZATION? - Kulchytska, G.; Gerasimets, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In syenites massifs of the Ukrainian Shield with rare-metal mineralization frequently zoned crystals have been observed, inner zone of which is composed of britholite and external one of allanite. More britholite is contoured by allanite in syenites of Azov stock in Peri-Azovian region, where this mineral forms commercial accumulations. Genesis of these formations was considered as a consequence of the replacement of britholite postmagmatic fluids, as a reaction product of britholite with surrounding aluminosilicates. The aim of this article is to propose another possible mechanism for the formation of zoned crystals of britholite in syenites of Azov intrusion. Salient features of britholite from syenites of Azov stock are a variety of secretions, variable chemical composition, phase and structural heterogeneity. Phase heterogeneity is emphasized by a large amount of solid-phase inclusions, crystalline and amorphous, including many iron oxides. Everywhere, britholite is contoured by rims of quartz the width of which on the border with amphibole is twice wider than the same one on the verge of alkali feldspar. Fluorite is attached to allanite in rims in ore zone. The article presents a number of facts showing no reaction of interaction between britholite and allanite and the presence of such with the host aluminosilicates. Attention is paid to britholite crystallization conditions. This is one of the earliest syenites minerals formed in conditions of high temperature (over 1000 °C) and pressure (500–200 MPa) due to heavy heterogenization melt caused by liquation processes. It is assumed that britholite is formed from individual drops of the salt melt silicate-fluoride-phosphate and silicate-phosphate composition, separated from the aluminosilicate melt. Fe-rich melt remains in liquates after crystallization britholite interacted with the surrounding aluminosilicate melt to form allanite. The formation of zonal crystals britholite with allanite rims around appears to be a natural consequence liquation and crystallization differentiation of magmatic melt in the Azov syenites intrusion.